STRATEGI PEMERINTAH DAERAH DALAM PENANGGULANGAN KEMISKINAN DI NUSA TENGGARA TIMUR - Hendrik Toda (Universitas Sultan Ageng Tirtayasa, 2016)
Poverty is a condition in which an individual or group of people under a decentstandard of living due to the lack of fulfillment basic needs such food, clothing, shelterand drinking water, which affects the quality of life. According to data from the CentralBureau of Statistics East Nusa Tenggara (NTT) the number of the poor in NTT toNovember 2014 reached 991.880 thousand people of the total number of people in NTTare 5.356.67 people spread in 22 counties and cities. Program StrategiPenanggulangan Kemiskinan has been done by the Local Government has entered thesecond period. Therefore, the government gives attention through flagship ProgramsDesa Mandiri Anggur Merah (DEMAM), which began in 2011-2015 for the NTT.Through this program is expected to bring changes to people's lives are scatteredthroughout the area in NTT. This program is intended for the 287 villages of a total of2,837 villages in NTT meaning that every village received a grant of 250 million pervillage and then given to groups of small businesses that have signed up to be membersof the cooperative, so it can be targeted. This research was conducted using qualitativedescriptors. Through this program, the government can help poor communities in NTTto improve the quality of life as well as the response of the eraser head in the area ofimproving public services and improve the competitiveness of the region by maximizingthe potentials that exist in the area for the public welfare.